Pattern of Musculoskeletal Disorders among Diabetic Patients Attending a Tertiary Care Hospital in Dhaka - Khan, Md Shah Zaman; Shakoor, MA; Moyeenuzzaman, Md; Islam, Md Quanurul (Ibrahim Medical College Journal, 2009)
Disorders of musculo-skeletal (MSK) system are common conditions seen in diabetic patients. The present study investigated the pattern of MSK disorders among the Bangladeshi diabetic patients attending the Department of Physical Medicine and Rehabilitation of a tertiary care hospital in Dhaka over a period of one year. A total of 2062 diabetic patients with MSK disorders were included in the study. Degenerative joint diseases were more common (53.2%) than inflammatory arthropathies (20.1%). Ibrahim Med. Coll. J. 2008; 2(2): 65-66 Key Words: Musculoskeletal (MSK) disorders, diabetic patients, BIRDEM doi: 10.3329/imcj.v2i2.2941